Inflammatory Breast Cancer: The Secretome of HCMV+ Tumor-Associated Macrophages Enhances Proliferation, Invasion, Colony Formation, and Expression of Cancer Stem Cell Markers - Mohamed, Hossam Taha; El-Sharkawy, Aya Ali; El-Shinawi, Mohamed; Schneider, Robert J.; Mohamed, Mona Mostafa (Frontiers in Oncology, 2022)
Inflammatory breast cancer (IBC) is a highly aggressive phenotype of breast cancer that is characterized by a high incidence early metastasis. We previously reported a significant association of human cytomegalovirus (HCMV) DNA in the carcinoma tissues of IBC patients but not in the adjacent normal tissues. HCMV-infected macrophages serve as “mobile vectors” for spreading and disseminating virus to different organs, and IBC cancer tissues are highly infiltrated by tumor-associated macrophages (TAMs) that enhance IBC progression and promote breast cancer stem cell (BCSC)-like properties. Therefore, there is a need to understand the role of HCMV-infected TAMs in IBC progression. The present study aimed to test the effect of the secretome (cytokines and secreted factors) of TAMs derived from HCMV+ monocytes isolated from IBC specimens on the proliferation, invasion, and BCSC abundance when tested on the IBC cell line SUM149. HCMV+ monocytes were isolated from IBC patients during modified radical mastectomy surgery and tested in vitro for polarization into TAMs using the secretome of SUM149 cells. MTT, clonogenic, invasion, real-time PCR arrays, PathScan Intracellular Signaling array, and cytokine arrays were used to characterize the secretome of HCMV+ TAMs for their effect on the progression of SUM149 cells. The results showed that the secretome of HCMV+ TAMs expressed high levels of IL-6, IL-8, and MCP-1 cytokines compared to HCMV- TAMs. In addition, the secretome of HCMV+ TAMs induced the proliferation, invasion, colony formation, and expression of BCSC-related genes in SUM149 cells compared to mock untreated cells. In addition, the secretome of HCMV+ TAMs activated the phosphorylation of intracellular signaling molecules p-STAT3, p-AMPKα, p-PRAS40, and p-SAPK/JNK in SUM149 cells. In conclusion, this study shows that the secretome of HCMV+ TAMs enhances the proliferation, invasion, colony formation, and BCSC properties by activating the phosphorylation of p-STAT3, p-AMPKα, p-PRAS40, and p-SAPK/JNK intracellular signaling molecules in IBC cells.